Incidence, etiology, sociodemographic and clinical characterization of acute respiratory failure in pediatric patients at a high-altitude city: A multicenter cohort study - Vargas Muñoz, Sarha M.; De Vivero Haddad, Sara; Beltran, Aldo M.; Bonilla Gonzalez, Carolina; Naranjo Vanegas, Melisa; Moreno-Lopez, Sergio; Rueda-Guevara, Paola; Barrera, Pedro; Piñeros, Juan Gabriel; Mejía, Luz Marina; Mesa, María Lucia; Restrepo-Gualteros, Sonia; et al. (Frontiers in Pediatrics, 2022)
Background: Acute respiratory failure is a life-threatening medical condition, associated with a variety of conditions and risk factors (1,2), including acute respiratory diseases which are a frequent cause of pediatric morbidity and mortality worldwide (3). In Colombia, the literature related to ARF is scarce. Objective: To determine the incidence, causes, and sociodemographic and clinical characteristics of ARF in three hospitals in Bogota, a high-altitude city located in Colombia, during the COVID-19 pandemic. Methods: A multicenter prospective cohort study called the FARA cohort was developed between April 2020 – December 2021. Patients older than one month and younger than 18 years with respiratory distress who developed ARF were included. Results: 685 patients with respiratory distress were recruited in 21 months. The incidence density of ARF was found to be 41.7 cases per 100 person-day CI 95%, (37.3-47.7). The median age was 4.5 years.. Most of the patients consulted during the first 72 hours after the onset of symptoms. Upon admission, 67.2% were potentially unstable. The most frequent pathologies were asthma, bronchiolitis, pneumonia, and sepsis. At admission, 75.6% of the patients required different oxygen delivery systems, 29,5% a low-flow oxygen system, 36,8% a high-flow oxygen system, and 9,28% invasive mechanical ventilation. SARS-COV-2, respiratory syncytial virus, rhinovirus/enterovirus, and adenovirus were the most frequently isolated viral agents. The coinfection cases were scarce. Conclusions: This multicenter study, the FARA cohort, developed at 2,600 meters above sea level, shows the first data on incidence, etiology, sociodemographic and clinical characterization in a pediatric population with ARF that also concurs with the COVID-19 pandemic. These results, not only have implications for public health but also contribute to the scientific and epidemiological literature on a disease developed at a high altitude. .